PERUBAHAN, PERGESERAN DAN PEMERTAHANAN BAHASA - Agus Supriyadi (Cakrawala Bahasa, 2020)
Language is one of the results of human culture and has a very significant role in social life. The purpose of this article articles is to find out about the change, shift and maintenance of a language. There are several theories that can be used as references in studying a language, especially those related to the topics and relevant examples. The factors that can influence the language change, shift and maintenance are economic, social and political factors, demographics, and attitudes and values.